Avaliação de fontes de informação na internet: critérios de qualidade - FERNANDES, Dayane Joyce (2021)
It presents criteria for evaluating sources of information, with the general objective of contributing to the reflection on the quality of information sources in the Internet and with specific objectives to conceptualize sources of information, considering their classification; understanding the internet as a means of accessing information sources; and analyze criteria for evaluating the quality of information sources on the Internet. For this, a bibliographical survey of methods of evaluation based on the existing literature on the topics of sources of information and criteria for evaluation of sources of information on the Internet was carried out, with the purpose of constructing the theoretical reference and identifying publications that presented evaluation criteria. As a result, four criteria were selected for the evaluation of Internet information sources, made available and elaborated by American Libray Association, Alexander and Tate, Smith and Tomaél et al. Criteria that facilitated the selection of information sources suitable for user use. It was concluded that these criteria allow to evaluate efficiently the sources of information available on the Internet, providing the necessary adaptations after the identification of fragilities in the sites after the use of the criteria.